Given the terms
-2, 4, -8, 16
The first term = -2
The second term is 4
The third term is -8
The fourth term is 16
We can observe that this is a geometric sequence
So to get the 11th term, we will first get the formula
Step 1: Get the common ratio (r)
![\text{common ratio=}\frac{\sec ond\text{ term}}{first\text{ term}}=\frac{third\text{ term}}{\sec ond\text{ term}}](https://img.qammunity.org/2023/formulas/mathematics/college/t7wnofocckighz1hxcg77wpt6xx44nt6is.png)
![r=(4)/(-2)=(-8)/(4)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/r1s2rd6g9qm1a6bjmel6iudg7lq0xw7zpg.png)
Step 2: Get the formula for the nth term
The formula is given by
![T=r^n](https://img.qammunity.org/2023/formulas/mathematics/college/bdkf9nr8bz76czdznrejte7zxa8k58lypj.png)
![T=(-2)^n](https://img.qammunity.org/2023/formulas/mathematics/college/5eeyrzc3xl68zgh0rpuivmx61zunp6a4rg.png)
where T is the nth term
n is the number of terms
Step 3: Find the 11th term
![T_(11)=(-2)^(11)](https://img.qammunity.org/2023/formulas/mathematics/college/2gw02flizic17s0hgn6zh7iry9y6b4x8cf.png)
![T_(11)=-2048](https://img.qammunity.org/2023/formulas/mathematics/college/t0z6ypbxublstabyxlmpme6koqw1ggwa0b.png)
The 11th term is -2048